지역약국 약사의 복약지도 현황 및 상담공간에 대한 인식 - 이해윤(Hae Yoon Lee), 한혜성(Hye Seong Han), 손현순(Hyun Soon Sohn) (Yaghag-hoi-ji, 2020)
Community pharmacists often need to communicate with private information during the medication counselingprocess with patients. This study aimed to survey current status of medication counseling and pharmacists’ perception onprivate counseling area in community pharmacies. 29-items questionnaire was used. Pharmacists working in communitypharmacies were enrolled during May to June 2018. Descriptive statistical analysis were conducted using Microsoft Excelprogram. Of 118 respondents, 80.5% were older than 40, 11.9% were 6-year educated pharmacists, and 65.2% worked insmall sized pharmacies less than 2 working pharmacists. 74.6% spent less than 3 minutes per prescription for medicationcounseling. 49.2% perceived their counseling is insufficient with major reasons of patients’ non-preference of detailedmedication guidance and lack of pharmacist time. 96.6% provided medication counseling at open general counter, while3.4% at general counter divided into partition and none at private counseling area. 61.9% experienced difficulties incounseling due to concerns about the leakage of patient's privacy. 51.7% agreed to necessity of private counseling areasuch as opaque partition for ensuring patient’s privacy. 57.6% agreed to set up a private counseling area in the future. Considering increased pharmacist role for caring patients in community and higher pharmacists’ perceptions on necessityof private counseling area, practical efforts to upgrade pharmacy’s space structure are expected. KCI Citation Count: 0